2019
DOI: 10.1186/s13031-019-0225-x
|View full text |Cite
|
Sign up to set email alerts
|

Programmatic implications for promotion of handwashing behavior in an internally displaced persons camp in North Kivu, Democratic Republic of Congo

Abstract: BackgroundDiarrhea and acute respiratory infections (ARI) account for 30% of deaths among children displaced due to humanitarian emergencies. A wealth of evidence demonstrates that handwashing with soap prevents both diarrhea and ARI. While socially- and emotionally-driven factors are proven motivators to handwashing in non-emergency situations, little is known about determinants of handwashing behavior in emergency settings.MethodsWe conducted a qualitative investigation from June to August 2015 in a camp for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 15 publications
(16 reference statements)
1
31
0
Order By: Relevance
“…Previously, studies done on handwashing in emergencies suggest that people likely adhere to their pre-emergency standards of hygiene. 29 Humans are creatures of habit, and this makes newly acquired behaviours fragile.…”
Section: Peer Reviewmentioning
confidence: 99%
“…Previously, studies done on handwashing in emergencies suggest that people likely adhere to their pre-emergency standards of hygiene. 29 Humans are creatures of habit, and this makes newly acquired behaviours fragile.…”
Section: Peer Reviewmentioning
confidence: 99%
“…19 A hand hygiene study with displaced adults in the Democratic Republic of Congo highlighted the role of emotional and social motivators and a need for innovation. 20 Physical distancing is not feasible in crowded settlements, 21 yet limited research has assessed strategies to promote alternatives such as household or community shielding. 3 22 Our study applies behavioural science to mobile health (mHealth) to increase COVID-19 preventive practice uptake with urban refugee youth.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…The kits aim to reduce the risk of disease transmission by encouraging increased levels of hygiene at the household level, but distribution of hygiene items has achieved mixed results in crisis settings (8,(12)(13)(14)(15). After increased soap provision in a South Sudanese refugee camp, handwashing with water only was more commonly observed (< 70%) than handwashing with soap (< 20%), although over 95% of participants reported that soap was available and more than 84% reported exposure to handwashing promotion where messages of the importance of soap had been shared (8).…”
Section: Introductionmentioning
confidence: 99%
“…After increased soap provision in a South Sudanese refugee camp, handwashing with water only was more commonly observed (< 70%) than handwashing with soap (< 20%), although over 95% of participants reported that soap was available and more than 84% reported exposure to handwashing promotion where messages of the importance of soap had been shared (8). In refugee camps in Sub-Saharan Africa and South-East Asia, handwashing facilities distributed to households or installed by camp management were found to be missing or not working (13)(14)(15). Provision of soap and handwashing facilities are only effective in protecting against disease if used as intended.…”
Section: Introductionmentioning
confidence: 99%